Language learning strategies used by successful and unsuccessful language learners in the process of learning English as a foreign language at the Transcarpathian Hungarian Institute named after Ferenc Rakoczi II - Szilágyi László; Siladi Vasyl; Сіладі Василь (PoliPrint Kft., 2009)
A nyelvtanulás során megválasztott tanulási stratégiák fontos részét képezik a sikeres nyelvtanulásnak. Különböző technikák és módszerek alkalmazása, mint: találgatás, induktív és deduktív tanulás, az új szavak osztályozása, a célnyelven való gondolkodás, idegennyelvű kiadványok olvasása mind a nyelvtanulási stratégiák kategóriába tartoznak. Jelen dolgozat a II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola angol szakos hallgatóinak a nyelvtanulási stratégiáját vizsgálja.

Резюме. Стратегії для навчання, обрані в процесі вивчання мови, відіграють важливу роль в успішному мови. Використання таких засвоєнні технік і методів, як здогадка, індуктивне та дедуктивне навчання, групування нових слів, читання на іноземній мови – все це відноситься до категорії стратегій вивчання мови. Дана робота досліджує стратегії навчання студентів англійської мови в ЗУІ.

Abstract. The subject matter of this paper is strategies used by successful and unsuccessful language learners in the process of learning English as a foreign language. The paper presents a research carried out at a Transcarpathian higher educational establishment, the main aim of which was to find out which language learning strategies are used by the students while learning English. The importance of such a research lies in that language learning which strategies might be the key to the success of each student in the learning process.
https://www.kmf.uz.ua/hun114/letoltes/acta/acta2009_1.pdf https://opac3.brff.monguz.hu:443/hu/record/-/record/123857
Keywords: language learning strategies; successful language learners; unsuccessful language learners; Transcarpathian Hungarian Institute named after Ferenc Rakoczi II